Proteomic analysis of a rare urinary stone composed of calcium carbonate and calcium oxalate dihydrate: A case report. (30th September 2013) - Kaneko, Kiyoko; Matsuta, Yosuke; Moriyama, Manabu; Yasuda, Makoto; Chishima, Noriharu; Yamaoka, Noriko; Fukuuchi, Tomoko; Miyazawa, Katsuhito; Suzuki, Koji
Abstract The objective of the present study was to investigate the matrix protein of a rare urinary stone that contained calcium carbonate. A urinary stone was extracted from a 34‐year‐old male patient with metabolic alkalosis. After X‐ray diffractometry and infrared analysis of the stone, proteomic analysis was carried out. The resulting mass spectra were evaluated with protein search software, and matrix proteins were identified. X‐ray diffraction and infrared analysis confirmed that the stone contained calcium carbonate and calcium oxalate dihydrate. Of the identified 53 proteins, 24 have not been previously reported from calcium oxalate‐ or calcium phosphate‐containing stones. The protease inhibitors and several proteins related to cell adhesion or the cytoskeleton were identified for the first time. We analyzed in detail a rare urinary stone composed of calcium carbonate and calcium oxalate dihydrate. Considering the formation of a calcium carbonate stone, the new identified proteins should play an important role on the urolithiasis process in alkaline condition.